Glutamate synthase 1 is involved in iron‐deficiency response and long‐distance transportation in Arabidopsis. Issue 12 (20th July 2020) - Cui, Man; Gu, Mengjun; Lu, Yaru; Zhang, Yue; Chen, Chunlin; Ling, Hong‐Qing; Wu, Huilan
Abstract: Iron is an essential microelement for plant growth. After uptake from the soil, iron is chelated by ligands and translocated from roots to shoots for subsequent utilization. However, the number of ligands involved in iron chelation is unclear. In this study, we identified and demonstrated that GLU1, which encodes a ferredoxin‐dependent glutamate synthase, was involved in iron homeostasis. First, the expression of GLU1 was strongly induced by iron deficiency condition. Second, lesion of GLU1 results in reduced transcription of many iron‐deficiency‐responsive genes in roots and shoots. The mutant plants revealed a decreased iron concentration in the shoots, and displayed severe leaf chlorosis under the condition of Fe limitation, compared to wild‐type. Third, the product of GLU1, glutamate, could chelate iron in vivo and promote iron transportation. Last, we also found that supplementation of glutamate in the medium can alleviate cadmium toxicity in plants. Overall, our results provide evidence that GLU1 is involved in iron homeostasis through affecting glutamate synthesis under iron deficiency conditions in Arabidopsis . Abstract : In this study, analysis of the Arabidopsis glutamate synthase 1 (glu1) mutant reveals that the amino acid glutamate is involved in iron homeostasis and acts as a molecular link between nitrogen metabolism and iron homeostasis.